ANALYSIS OF THE PRICE-MECHANISM ON THE OIL MARKET OF KAZAKHSTAN - D.Е. Satenova,; A.E. Agumbayeva, (Academic Journal of Physical and Chemical Sciences, 2019)
The oil industry of Kazakhstan is not only the most important industry, it is one of the main components of the economic security of the country, its independence. Tax revenues from the development of oil fields and the sale of oil allow for the implementation of social programs and strengthen domestic political stability. Oil export from Kazakhstan is the most important factor in expanding world economic relations, including the country in globalization processes, and implementing not only economic interests, but also political goals. The choice of the route for export oil pipelines will largely determine Kazakhstan’s foreign policy and foreign economic strategy.